2021
DOI: 10.32854/agrop.v14i12.2148
|View full text |Cite
|
Sign up to set email alerts
|

Laelia anceps Lindl. (Orchidaceae) adaptation on phorophytes within an anthropized landscape, Amatlán de los Reyes, Veracruz, Mexico

Abstract: Objective: To determine the best phorophyte species for the adaptation of the Laelia anceps Lindl orchid. (Orchidaceae) in an anthropized landscape. Design/methodology/approach: A completely randomized experimental design with four treatments (phorophytes) was used: Swietenia macrophylla King., Fraxinus sp., Persea schiedeana Nees. and Tecoma stans. (L.) Juss. ex Kunth), with five repetitions per phorophyte and with three L. anceps orchid plants in each phorophyte. The following variables were measured: day to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…(2021), and Hernandez‐Garcia et al . (2021). However, the quantification of bark roughness in previous works has never been standardized and is problematic in many other ways (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021), and Hernandez‐Garcia et al . (2021). However, the quantification of bark roughness in previous works has never been standardized and is problematic in many other ways (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, trees with flaky or peeling bark are considered to be poor sites for attachment because plants can be easily detached together with the unstable substrate (ter Steege & Cornelissen, 1989;Hietz & Hietz-Seifert, 1995;Malizia, 2003;Wyse & Burns, 2011). 'Rougher bark' has been positively linked to epiphyte establishment since the classic works of Schimper (1888), Oliver (1930), and Went (1940), and the idea has been perpetuated in more recent works such as that from Hern andez-P erez et al (2018), Adhikari et al (2021), andHernandez-Garcia et al (2021). However, the quantification of bark roughness in previous works has never been standardized and is problematic in many other ways (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The plants will reach a height of 15 cm from the base of the pseudobulb to the tip of the largest leaf and their roots will reach 10 cm in length on average, as in Lycaste aromatica (Figure 7B and 7C), as indicators of survival. Hernández-García et al (2021) reported they successfully established 30 specimens of Laelia anceps in ash (Fraxinus sp.) and Creole avocado (Persea sp.)…”
mentioning
confidence: 99%